PENGARUH MINAT BELAJAR SISWA TERHADAP KEMAMPUAN REPRESENTASI SISWA - Riyanti, Riyanti; Rosyadi, Rosyadi; Nurafifah, Luthfiyati (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2023)
This study aims to determine: (1) the effect of students' learning interests on students' mathematical representation abilities, (2) the closeness of the relationship between students' learning interests on students' mathematical representation abilities, and (3) the relative size of the influence of students' learning interests on students' mathematical representation abilities in SPLDV material . The method used in this study is descriptive quantitative using statistical calculations Regression Test to determine the effect of student motivation on the mathematical representation abilities of grade 8 students. The samples taken were grade 8B students of SMP Negeri 1 Sindang. The data analysis technique in this study used non-linear regression analysis. The results of this study are: (1) Students' interest in learning does not affect students' mathematical representation abilities; (2) There is a relationship between student learning interest and mathematical representation ability in SPLDV material of so that the correlation level is very low in achieving student learning interest; and (3) The relative contribution of student learning interest to the ability of mathematical representation in SPLDV material is 0.0064%.